Pathological Crying and Laughing in Motor Neuron Disease: Pathobiology, Screening, Intervention - Finegan, Eoin; Chipika, Rangariroyashe H.; Li Hi Shing, Stacey; Hardiman, Orla; Bede, Peter (Frontiers in Neurology, 2019)
Pathological crying and laughing (PCL) has significant quality-of-life implications in amyotrophic lateral sclerosis (ALS); it can provoke restrictive life-style modifications and lead to social isolation. Despite its high prevalence and quality of life implications, it remains surprisingly understudied. Divergent pathophysiological models have been proposed, centred on corticobulbar tract degeneration, prefrontal cortex pathology, sensory deafferentation, and impaired cerebellar gate-control mechanisms. Quantitative MRI techniques and symptom-specific clinical instruments offer unprecedented opportunities to elucidate the anatomical underpinnings of PCL pathogenesis. Emerging neuroimaging studies of ALS support the role of cortico–pontine–cerebellar network dysfunction in context-inappropriate emotional responses. The characterisation of PCL-associated pathophysiological processes is indispensable for the development of effective pharmacological therapies.